1b - Introduction: New Approaches to Social Movements and Human Rights - Luca Bussotti,; Redy Wilson Lima,; Remo Mutzenberg, (Africa Development, 2025)
The project that led to this issue emerged in Recife, during the 3rd Conference on Activism in Africa, held in September 2021 in online format owing to restrictions related to the pandemic. The three organisers of this issue took part in the conference, co-ordinating panels and proposing papers along the theme of social movements and their demands in the defence of human rights. In the process they identified the fundamental axes for building an intellectual link and civic commitment between Africa and Brazil. Therefore, in 2024 we decided to organise a special issue on topics re- lated to the Portuguese-speaking global South. We were keenly aware that this would be a challenge, for several reasons. First, scientific production in the Portuguese-speaking African countries (PALOP) is still below par. Second, we wanted to go beyond the generally institutional representations of these countries, including studies on the Afro-Brazilian reality. There are numerous studies on bilateral or multilateral relations within the Community of Portuguese Language Countries (CPLP) and the activities of various national governments. However, they avoid uncomfortable subjects such as LGBTQAI+ in the PALOP or the failure of many Portuguese-speaking countries, especially in Africa, to protect the human rights of their citizens or migrant populations. This is the context for our effort to create this intellectual link between the epistemological, historical and sociological universes on both sides of the Atlantic and the African Indian Ocean, the connections between which are more alive today than ever before. The articles presented in this issue share this underlying inspiration: they propose an inward-looking approach to endogenous issues, developed through paradigms related to the two major areas of social movements and human rights featured here, but with an innovative, original and even un- precedented perspective. This perspective is of the global peripheralisation of the Portuguese-speaking global South, highlighting challenges at a local level – for example, regarding the actions of PALOP governments in terms of their lack of respect for the most basic human rights. Our task was to look for texts that were coherent with the general theme of the issue, capable of cutting across and differentiating between the various countries considered, each with its own peculiarities, but without forgetting the common backdrop – the global and local processes of marginalisation, the resistance struggles, proposals for new epistemologies and breaking with the old paradigms that still dominate. Thanks to the dedication and collaboration of CODESRIA colleagues and the entire Africa Development team, it was possible to bring this project to a successful conclusion. This was despite the complications and challenges arising from having three organisers come from three different countries – Mozambique, Cape Verde and Brazil. A significant feature of this issue is the prevalence of female authors. In fact, 6 of the 11 colleagues who wrote or co-wrote the studies presented here are female researchers, most of them Black and African, a result that was not anticipated when we decided to go ahead with this issue. Given the marginal or ancillary role of women in many African academic centres, including Afro-Brazil, as the volume edited by Sapong and Amoako, The Palgrave Handbook of African Women’s Studies (2021), reminds us, the high proportion of female authors in this collection is even more important. In this way, it was possible to create the links we were looking for, in terms of both the presentation of the articles and the themes they covered. The critical and innovative approach is present in the first article of the is- sue, by Afro-Brazilian colleagues Luís Soares, Rayza Silva and Ana Cláudia Rodrigues da Silva, entitled ‘Vivências em Epistemologias Negras: desafios e perspectivas no ensino de Ciências Sociais na Universidade Federal de Pernambuco (UFPE)’. The study is an analysis of the subject ‘Black episte- mologies’ by three researchers – an anthropology lecturer, a Master’s student and a doctoral student at the Federal University of Pernambuco (UFPE), all of them Black. It seeks to innovate the epistemological horizon of UFPE’s social sciences curriculum. The authors define these courses as still having ‘a conservative and not very diverse profile’. In this article, they attempt to restore Black authors and epistemologies long forgotten or neglected by the ‘official’ Brazilian social sciences, in which ‘whiteness’ represents, as the authors argue, not only a physical condition but also, and above all, a historical and cultural legacy that they are trying to overcome. The dialogue with this work is noticeable in all the other studies presented here, which provide an overview of some of the PALOP (Angola, Mozambique and Cape Verde), with different epistemological perspectives but with a common aim. Largely, this is to deconstruct the preconceived and ‘targeted’ stereotypes (whether on the part of international donors or local governments, in many cases authoritarian) that prevail internationally, which distort the realities that are lived in the PALOP today. This is the case of the article by Osvaldo de Carvalho Cruz, entitled ‘Possibilidades e limites ao exercício da Liberdade Sindical em Cabo Verde de 1975 a 2014’. From the perspective of protecting human rights, which today are more and more neglected and out of fashion, this study aims to understand how limitations to trade union freedoms were put in place in Cape Verde by the successive governments that led the country and by economic organisations opposed to the working class. As the author explains, the exercise of trade union freedom is a relatively recent right in Cape Verde, dating back to the democratic turn of the 1990s, which led to the division of the single trade union centre (UNTC-CS) into seven labour rights movements, some of them antagonistic to each other. Despite the advent of democracy and Cape Verde’s international reputation as a democratic and tolerant country, the author emphasises that the archipelago was among the countries that violated CILS (International Confederation of Free Trade Unions (ICFTU)) trade union rights between 1992 and 2000. Some partial improvement was achieved in the following 15 years, but still with significant limitations. This article shows how real social dynamics are far removed from what is laid down in the Constitution and labour laws. Thus, even a model African country like Cape Verde deserves critical analysis, especially in terms of the achievement of fundamental rights, such as trade union rights. Also discussing fundamental rights and the struggles to overcome their violations is the article by Maria Elvira Carlos Chipe, Rosana Albuquerque and Maria José Núncio, entitled ‘A protecção social e a sua evolução no direito internacional: Um olhar sobre Moçambique’. It analyses Mozambique’s social protection mechanisms, in which the ‘informal’ system, which is community and family-based, makes up for the shortcomings of the formal system in a country where the poverty rate has skyrocketed in recent years, affecting more than 60 per cent of its population, according to official national statistics. It concludes by pointing out that the Mozambican government should draw up a more realistic strategy that is coherent with the country’s complex reality and makes the formal social protection system more efficient and comprehensive. Laura António Nhaueleque writes about legislative, political and social rights and ambiguities in her study, ‘Uma longa ambiguidade: minorias sexuais em Moçambique entre tolerância e marginalização’. The subject of sexual minorities is tackled rarely, and is somewhat of a taboo in the panorama of human rights studies in Mozambique and in all the PALOP countries in general, signalling, in this case, a considerable difference with the Brazilian reality. In her study, the author focuses on LAMBDA, the main (and for a long time the only) Mozambican LGBTQIA+ rights association founded in 2006, which has yet to be formally recognised by the Mozambican government. With the help of an interview with one of LAMBDA’s leaders, the author tries to unravel the ambiguities of a relationship in which LAMBDA collaborates with the government on various fronts, mainly with the Ministry of Health, but without the latter recognising it formally. It is a clear example of ambiguity and incoherence on the part of local Mozambican authorities. The following article is also critical of non-governmental organisations and their complex relationship with international donors and Mozambican public institutions. ‘Organizações da Sociedade Civil em Moçambique: a “transmissão da dependência” e o papel das entidades intermediárias’, by Ernesto Nhatsumbo and Luca Bussotti, looks at a subject that is not often covered in the vast literature on civil society in Mozambique – that of ‘intermediary organisations’ such as MASC and JOINT (civil society support institutions). These organisations place themselves in the political and financial space between donors (usually Western) and local grassroots associations, receiving and distributing funds, and acting (according to the authors) as a continuation of the external dependency mechanism of most NGOs in that country. The result is that most Mozambican civil society organisations not only fail to be sustainable from a financial point of view but, above all, their agendas and their implementation are subordinated to the dictates of donors and intermediary bodies such as MASC and JOINT. This makes them increasingly unable to work in line with the demands of the communities they are supposed to be representing. Gilson Lázaro’s article takes us back to the Angolan context and the dynamics of its youth movements. In his article, ‘Dinâmicas dos movimentos juvenis: Protestos de rua e Contestações nas redes sociais em Angola’, Lázaro seeks to study how collective action with ‘new’ content, by young Angolans, breaks with the country’s autocratic tradition and proposes different perspectives. The article specifically discusses moments identified by the author as central to Angola’s social and political dynamics. On the one hand, there are those that relate to symbolic dates in national history; on the other, there are those connected with spontaneous movements – two pre-electoral and one electoral – which initially manifested themselves on social networks. The article concludes by highlighting the growing maturity of these movements, led by young people who are using their constitutionally established rights as leverage to demand greater electoral transparency and respect for the will of the people in choosing their leaders. At the same time, these movements focus on revisiting memory and challenging the monopoly of official historiography, which is now being deconstructed. We believe that this special issue on PALOP and Afro-Brazil is an import- ant point of reference for anyone who wants to study social movements and human rights outside of the sometimes pompous, sometimes ‘institutional’, rhetoric present in many existing discourses and publications. The critical perspective common to all the articles published here is that complex processes relating to realities that have not yet been sufficiently studied require innovative and multifaceted approaches and methodologies that are not reductionist or positivist, or centred on the cause–impact binomial. The hope is that the themes and approaches of these articles will stimulate interest, debate and polemics. If this is the outcome, we will have achieved the main objective of this issue.